Habiter la sphère du loisir : Réflexions conceptuelles et perspectives empiriques. Issue 1 (2nd January 2021) - Roult, Romain; Lapointe, Marie-Claude; Prévost, Anne-Sophie
ABSTRACT: In today's society, considered hypermodern by some, the concepts of experience, pleasure and enjoyment are predominant, and very frequently tinged with consumerism. Leisure therefore takes center stage in everyday settings, fragmented both temporally and spatially. In the form of an essay, this article discusses two concepts shown to be insightful analytical tools for decoding these renewed socio-territorial mechanisms. The concepts of dwelling and sphere are defined and linked to leisure with a view to furthering fundamental thinking in this area. In parallel, the article empirically illustrates our thinking approach in a study of travel among young Quebecers which highlights how leisure helps (people) reconnect with one form of interior space and at the same time open up to the Other through the mechanisms of connecting and distancing.